Analysis of reproductive traits and laying egg rhythm of maize weevil sitophilus zeamais (motschulsky) - Duong, Nguyen Van; Long, Khuat Dang; Que, Le Xuan (Academia Journal of Biology, 2019)
The maize weevil, Sitophilus zeamais (Motschulsky), is a serious pest affecting a wide range of cereal crops, such as maize, rice, beans and other stored dried grains. As a S. zeamais female can keep laying eggs for a long time throughout its life after chewing its way into the grains, most development stages of the maize weevil, such as eggs, larvae and pupae, can always be found in stored maize grains. Our experiment with S.  zeamais on long grain rice showed that 10 days after eclosion and mating, maize weevil females started laying eggs for a period of 145 days. On average, a S.  zeamais female laid 38.67 eggs, of which, up to 62.81% were laid in the first 7–8 weeks (with the remaining 37.19% in the latter half of the 145 day period), and 55.07%  were laid within day 55–95. The egg laying pattern of S. zeamais was modeled using cubic polynomials, which described the maximum percentages of eggs laid at day 15, 35, 75, 95 and 105.